Macroeconomics: Principles, Problems, and Policies - L. Brue Stanley (Mc Graw Hill, 2005)
Revisions of previous books by the authors on macroeconomics and microeconomics. They have been updated to reflect the latest developments in economics. They feature a fully integrated global perspective and a new design and art programme.